2017
DOI: 10.1111/cdoe.12327
|View full text |Cite
|
Sign up to set email alerts
|

Risk of subsequent attention‐deficit/hyperactivity disorder among children and adolescents with amalgam restorations: A nationwide longitudinal study

Abstract: Objectives: Dental amalgam has been used as a common restorative material since the 1800s, but concerns have been raised regarding its purported neuropsychological effects due to the neurotoxicity of mercury. In this study, a nationwide population-based database was employed to investigate the association of dental amalgam restoration with the risk of attention-deficit/hyperactivity disorder (ADHD). Results: In total, 2073 people (2.4%) received an ADHD diagnosis during the study period, yielding an incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…A recent study by Lin et al conducted in a sample of 80,000 mothers in the United States showed that although there was a weak positive association between the presence of amalgam restorations and ADHD, there was insufficient evidence to establish any meaningful relationship. 19 The results of our study seem to support this hypothesis and are in keeping with the studies of Karouna-Renier et al 9 and Van Wijngaarden et al 11 that suggest a low level of evidence between prenatal mercury level and ADHD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A recent study by Lin et al conducted in a sample of 80,000 mothers in the United States showed that although there was a weak positive association between the presence of amalgam restorations and ADHD, there was insufficient evidence to establish any meaningful relationship. 19 The results of our study seem to support this hypothesis and are in keeping with the studies of Karouna-Renier et al 9 and Van Wijngaarden et al 11 that suggest a low level of evidence between prenatal mercury level and ADHD.…”
Section: Discussionsupporting
confidence: 93%
“…Salivary analysis of mercury provides a relatively easy measure to compare mercury levels in children with ADHD and those without ADHD. [15][16][17][18] While few studies have successfully shown increased mercury levels in the blood, urine, and saliva of individuals with ADHD, 13,14,19 there has been no systematic attempt made to evaluate the age, demographic, or oral health factors that could influence the levels of mercury in the saliva of children with ADHD when compared to age-and gender-matched controls.…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference in age or sex was observed between the sampled group and all enrollees in the country's health insurance program. This database has been adopted in many longitudinal epidemiological and cost‐effectiveness studies .…”
Section: Methodsmentioning
confidence: 99%
“…One study used a nationwide database of more than 88 000 young people to investigate the association between amalgam restorations and attention-deficit/hyperactivity disorder (ADHD). 253 Children with one or more restorations and no ADHD history before 2001 were tracked through 2011 for a positive diagnosis of ADHD. In total, 2073 (2.4%) received a positive ADHD diagnosis yielding an incidence rate of 32.4 per 100 000 person-years, but there was no significant difference between those receiving amalgam and composite resin restorations.…”
Section: Amalgammentioning
confidence: 99%